Full recovery of brines at normal temperature with process-heat-supplied coupled air-carried evaporating separation (ACES) cycle - Jing Yu; Yujiang Xia; Liang Chen; Weidong Yan; Baobin Liu; Sumin Jin (npj Clean Water)
Abstract Conventional air-carried evaporating separation (ACES) technology, to achieve complete separation and recovery of water and salt in brine, tends to necessitate heating air above a critical temperature (typically>90 °C). In this paper, a novel concept of process-heat-supplied and an ACES cycle with this technique is proposed. A comprehensive thermodynamic analytical investigation is conducted. The results indicate that at heat source supply temperature T supply of only 45.17 °C, this novel unit is capable of achieving complete separation of water and salt from 5 wt% concentration brine. Meanwhile, thermodynamic mechanism analysis reveals that sufficient process-heat-supplied affords the fluid self-adaptive regulation on the driving potential of heat and mass transfer, thus circumventing traditional heat and mass transfer limitation. Additionally, a solar ACES system with process-heat-supplied incorporating heat pump is further proposed. For this system, theoretical evaporation rate for unit area of solar irradiation m e-solar = 2.23 kg/(m2·h), integrated solar utilization efficiency η i = 188%; while considering overall losses m e-solar = 1.41 kg/(m2·h), η i = 95.2%.